2019
DOI: 10.7759/cureus.6041
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Drug-induced Sleep Endoscopy on Therapeutic Decisions in Obstructive Sleep Apnea: A Systematic Review and Meta-analysis

Abstract: ObjectiveThe aim of this study was to assess the ability of drug-induced sleep endoscopy (DISE) to change therapeutic decisions through the identification of obstruction sites in patients with obstructive sleep apnea (OSA).Materials and methodsA systematic review and meta-analysis were conducted concerning studies that reported the impact of DISE on therapeutic recommendations. The percentage of change was collected for each study and per site of the collapse. The pooled rate of change and the respective 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…DISE enables direct visualization of dynamic airway changes and, therefore, permits delineation of the site of obstruction and subsequent treatment planning [104]. As mentioned, DISE has rapidly gained momentum and the indications and guidelines for the use of this technique will likely emerge in the upcoming years [105][106][107][108][109][110]. At this point, it is routine clinical practice in children with residual OSA after T&A to initially offer PAP therapy and medical therapy, and when patients are either unable, unsuccessful, or unwilling to adopt such options, then use of DISE-directed surgical therapies seems a logical and reasonable step, notwithstanding its limitations [111,112].…”
Section: Drug Induced Sleep Endoscopymentioning
confidence: 99%
“…DISE enables direct visualization of dynamic airway changes and, therefore, permits delineation of the site of obstruction and subsequent treatment planning [104]. As mentioned, DISE has rapidly gained momentum and the indications and guidelines for the use of this technique will likely emerge in the upcoming years [105][106][107][108][109][110]. At this point, it is routine clinical practice in children with residual OSA after T&A to initially offer PAP therapy and medical therapy, and when patients are either unable, unsuccessful, or unwilling to adopt such options, then use of DISE-directed surgical therapies seems a logical and reasonable step, notwithstanding its limitations [111,112].…”
Section: Drug Induced Sleep Endoscopymentioning
confidence: 99%
“…Interestingly, Albdah et al [ 38 ] in a systematic review and meta-analysis observed that DISE plays a significant role in changing the initial treatment surgical options in about fifty percent of OSA patients, particularly for epiglottis involvement and soft palate surgical procedures. The change in surgical treatment was more significant when midazolam was applied during DISE compared to other sedation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The present pilot study offers a small-scale but clinically interesting opportunity to evaluate the efficacy of dexmedetomidine in a real-life scenario, highlighting some of the strengths and shortcomings of a drug that has received attention in several settings (operative sedations, intraoperative use, critical care): in the context of DISE, dexmedetomidine continues to attract some interest, especially by nonexperts, as an agent hypothetically preventing deeper and longer desaturations. Therefore, we aimed to assess whether dexmedetomidine, in light of its pharmacodynamic properties, could replace propofol for DISE if needed or preferred, and with the main purpose to assess the timing and quality of peripheral oxygen desaturations, in respect of the procedure goals, that is the reproduction of airway obstruction patterns for the identification of the ideal surgical intervention [9,10] . Propofol has consistently established itself as the gold standard for sedation in this setting as it combines overall safety and time effectiveness.…”
Section: Discussionmentioning
confidence: 99%